CPW-Fed Transparent Antenna for Vehicle Communications - Jorge Iván Trujillo-Flores; Richard Torrealba-Meléndez; Jesús Manuel Muñoz-Pacheco; Marco Antonio Vásquez-Agustín; Edna Iliana Tamariz-Flores; Edgar Colín-Beltrán; Mario López-López (Applied Sciences, 2020)
In this paper, a fully transparent multiband antenna for vehicle communications is designed, fabricated, and analyzed. The antenna is coplanar waveguide-fed to facilitate its manufacture and increase its transmittance. An indium-tin-oxide film, a type of transparent conducting oxide, is selected as the conductive material for the radiation path and ground plane, with 8 ohms/square sheet resistance. The substrate is glass with a relative permittivity of 5.5, and the overall dimensions of the optimized design are 50 mm × 17 mm × 1.1 mm. The main antenna parameters, namely, sheet resistance, reflection coefficient, and radiation diagram, were measured and compared with simulations. The proposed antenna fulfills the frequency requirements for vehicular communications according to the IEEE 802.11p standard. Additionally, it covers the frequency bands from 1.82 to 2.5 GHz for possible LTE communications applied to vehicular networks.